Incidence of Irvine Gass Syndrome after Phacoemulsification with Spectral-Domain Optical Coherence Tomography. (17th November 2019) - Bellocq, David; Mathis, Thibaud; Voirin, Nicolas; Bentaleb, Zainab Machkour; Sallit, Rebecca; Denis, Philippe; Kodjikian, Laurent
ABSTRACT: Purpose : Incidence of significant and non-significant macular edema found using spectral-domain optical coherence tomography (SD-OCT) following cataract surgery. Methods : Prospective, cohort series conducted at the Croix Rousse University Hospital. Significant macular edema (SME) was defined as the presence of fluid with an increase of 30% or more in central subfield macular thickness compared to baseline on SD-OCT at 6 weeks and non-significant macula edema (NSME) as an increase of less than 30%. Results : Nine hundred and twenty-eight eyes in 638 patients were included in the study. Incidence of Irvine Gass (IG) syndrome was 9%, 2.3% of patients presented SME, 6.8% NSME. Epiretinal membrane, diabetes, and capsular rupture were significantly associated with a risk of IG. The risk of developing IG in the fellow eye was 23% in cases of IG in the first eye. In total 8.4% of all included patients developed chronic IG (duration of more than 6 months). Conclusion : This study reports the incidence of IG during 6 months of surgical activity at a French university hospital center.